Effects of family functioning on socioemotional behaviour of children in low income family - Arshat, Zarinah; Ismail, Zanariah; Omar, Rosmaria (RMP Publications, 2018)
This study examines the effects of family functioning on socioemotional behavior of children in low income family. Participants comprised of 518 parents of children aged four to six years old of low income family. Data were collected using structured questionnaires. Family functioning was measured using Malaysian Family Strengths Scale, while socioemotional behavior of children was measured using Strengths and Difficulties Questionnaire (SDQ). The findings of the study revealed that high level of family functioning contributed to low level of socioemotional behavior problems of children. Mothers and fathers of low income family had similar perception in family functioning and children socioemotional behavior. This study highlights the importance of enhancing family functioning in order to reduce emotional problems, conduct problems and peer problems and also incerasing prosocial behavior of children in low income family.